Use of archival images in mini-series “based on real events”: Spanish drama productions between 1990 and 2010 (Communication & Society, 2020)
Spanish series production between 1990 and 2010 (from the analogue switch-off to deregulation and the arrival of new TV channels and platforms) stands out for a large number of “based-on-real-events” dramas. These include historical events, traumatic events of little historical import and biographical accounts of eminent figures. This paper analyses the veracity of archival footage and other media resources (press, radio) included in these series and the way in which they used. A quantitative and qualitative analysis, combined with an extensive literature review, shows that some of the apparently real historical footage and images integrated into these series are in actual fact fake. The viewer’s possible confusion in decoding these images would suggest that the use of archival material in fictional drama brings it closer to genres traditionally considered non-fiction. Finally, the inclusion of real (and fake) archival footage in audio-visual accounts of past events appears to fulfil an ideological function.